Meton of Athens: An Astronomer in the Democratic Landscape of the Polis - García Quintela, Marco V. (Gerión. Revista de Historia Antigua, 2022)
The Athenian democracy of the 5th century BC saw a blossoming of knowledge. Some was closely associated with the institutions, with locations that were defined in the urban topography, while the new knowledge is more difficult to pinpoint. However, two testimonies situate the astronomer Meton in the Pnyx (Philoch. FGH 328 F 122) and in the theatre of Dionysius (Ar. Nu. 992-1020) meaning that he appeared before large audiences. This situation allows us to explore the social perception of new knowledge in Athens, and to understanding the unique mixture of realism and humour expressed by Aristophanes.